1980
DOI: 10.1080/03015521.1980.10426241
|View full text |Cite
|
Sign up to set email alerts
|

Rates of dairy shed effluent applied to pastures on clay soils in Northland

Abstract: Dairy shed washdowns were collected and sprayed on to pasture at two rates over four consecutive milking seasons from 1972 to 1976 on a farm near Whangarei. The high rate of effluent disposal (120000 l/ha every 21 days) increased mean annual herbage yields by 43% and the lower rate of disposal (60000 l/ha every 21 days) increased yields by 27%. Yield increases were obtained to effluent application throughout each milking season, provided pasture growth was not limited by moisture stress. The responses are main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 7 publications
(4 reference statements)
0
13
0
Order By: Relevance
“…Much of the earlier New Zealand-based research on FDE was carried out during a 4-year study on a Northland farm from 1972 to 1976 (Goold 1980). High and low application rates of FDE (12 mm and 6 mm applied every 21 days, respectively) were compared with water only (at the low rate) and control treatments.…”
Section: Studies Of Farm Dairy Effluent In New Zealandmentioning
confidence: 99%
“…Much of the earlier New Zealand-based research on FDE was carried out during a 4-year study on a Northland farm from 1972 to 1976 (Goold 1980). High and low application rates of FDE (12 mm and 6 mm applied every 21 days, respectively) were compared with water only (at the low rate) and control treatments.…”
Section: Studies Of Farm Dairy Effluent In New Zealandmentioning
confidence: 99%
“…Various studies have shown that the return of animal excreta to pasture, as urine, dung, slurry, or effluent, can have a beneficial effect on DM production (e.g., Goold 1980;Hogg 1981;Ledgard & Saunders 1982;Williams & Haynes 1995). However, as mentioned above, when excreta are returned to pasture in concentrated urine and dung patches, the quantities of N returned greatly exceed the plant requirements in the area of the patch.…”
Section: Effect Of Uneven Return Of Excreta On Pasture Productionmentioning
confidence: 94%
“…In a New Zealand grass/clover pasture, Goold (1980) measured an increase in DM production following spray irrigation of farm dairy effluent on a Waikare clay soil. Averaged over a 4-year period, annual DM production increased by 27% and 43% following effluent application every 21 days at 6 mm ha • (low) or 12 mm ha" 1 (high), respectively.…”
Section: Apparent N Efficiency: Slurry or Farm Dairy Effluentmentioning
confidence: 99%
See 1 more Smart Citation
“…More information is available on the disposal of other agricultural wastes. For example, silage effluent (Cooper 1977) and dairyshed effluent (Goold 1980) were found to be valuable sources of nutrients for grassland pastures. Large amounts of cattle-feedlot wastes, applied over a 5-year period, were shown to have no deleterious effects on soil microorganisms in cropland (Davis et a1.…”
Section: Introductionmentioning
confidence: 99%